1982
DOI: 10.1002/1097-0142(19820315)49:6<1258::aid-cncr2820490630>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastrointestinal lymphoma:A 30-year review

Abstract: The authors reviewed all cases of non-Hodgkin's lymphoma primarily involving the gastrointestinal tract treated at Memorial Hospital during the period from 1949-1978. Complete clinical records were available in 104 cases. Slides of original pathology specimens were available in 81 cases. Tumors were classified by Rappaport, Lukes-Collins and modified Kiel classifications. All patients were staged retrospectively, using modified Ann Arbor staging. The primary tumor was in the stomach in 76 patients, in the smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
56
0
3

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(74 citation statements)
references
References 15 publications
14
56
0
3
Order By: Relevance
“…12,19 Chronologic periods significantly influenced OS, but not EFS in our study. Weingrad et al 9 showed a similar time trend toward a better survival in the latest than the earliest period. However, a better OS may have been biased by differences in the length of follow-up and by the number of deaths unrelated to lymphoma.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…12,19 Chronologic periods significantly influenced OS, but not EFS in our study. Weingrad et al 9 showed a similar time trend toward a better survival in the latest than the earliest period. However, a better OS may have been biased by differences in the length of follow-up and by the number of deaths unrelated to lymphoma.…”
Section: Discussionmentioning
confidence: 79%
“…A better prognosis for gastric lymphoma compared with other localizations has been described previously, 1,4,8,11,17,18,21,24,25 although several authors showed no difference in the prognosis between gastric lymphoma and intestinal lymphoma. 5,9,[13][14][15]19,20,22,23 Few publications have shown prognostic data on patients with both gastric and intestinal involvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with a digestive site discovered during staging investigations of a NHL were excluded from the study. The mesenteric localizations were considered to be primary intestinal NHL in accordance with the literature (Otter et al, 1989aWeingrad et al, 1982Dragosics et al, 1985).…”
Section: Materials and Methods Patientsmentioning
confidence: 83%